Penser et construire l’espace tojolabal à travers une expérience rituelle transfrontalière (Mexique-Guatemala) - Carine Chavarochette (Ateliers d'Anthropologie)
The southeast Mexican state of Chiapas is home to Tojolabal Maya populations. One of the mythical origins of this group takes place in Guatemala in the Cuchumatanes mountains, in an area inhabited by another Maya group: the Chuj. Since the 1910-1920 Mexican revolution and the land reforms introduced by the government, the Tojolabal have been maintaining relations with the Chuj in the neighbouring country through rituals. By choosing to travel to Guatemala, the Tojolabal pilgrims cross not only a political and state boundary, they construct and give meaning to their territory by the very fact of crossing limits. The evolution of the religious itinerary and practices throughout the 20th century testify to the political events experienced by these populations.